2016
DOI: 10.5562/cca2908
|View full text |Cite
|
Sign up to set email alerts
|

Seryl-tRNA Synthetases in Translation and Beyond

Abstract: Abstract:For a long time seryl-tRNA synthetases (SerRSs) stood as an archetypal, canonical aminoacyl-tRNA synthetases (aaRS), exhibiting only basic tRNA aminoacylation activity and with no moonlighting functions beyond protein biosynthesis. The picture has changed substantially in recent years after the discovery that SerRSs play an important role in antibiotic production and resistance and act as a regulatory factor in vascular development, as well as after the discovery of mitochondrial morphogenesis factor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 113 publications
(204 reference statements)
0
6
0
Order By: Relevance
“…Aminoacyl-tRNA synthetases are therefore housekeeping proteins that play an important role in the expression of genes to create proteins. Besides that, aaRSs may be involved in a myriad of other cellular processes exerting their noncanonical function beyond translation (Guo et al 2013, Mocibob et al 2016. It is well documented that aaRSs participate in cellular stress responses in bacteria and metazoa.…”
Section: Introductionmentioning
confidence: 99%
“…Aminoacyl-tRNA synthetases are therefore housekeeping proteins that play an important role in the expression of genes to create proteins. Besides that, aaRSs may be involved in a myriad of other cellular processes exerting their noncanonical function beyond translation (Guo et al 2013, Mocibob et al 2016. It is well documented that aaRSs participate in cellular stress responses in bacteria and metazoa.…”
Section: Introductionmentioning
confidence: 99%
“…Canonical function of seryl‐tRNA synthetase (SerRS) in translation is aminoacylation of tRNA Ser with serine . In majority of organisms, but not in plants , SerRS attaches serine to the selenocysteine‐specific tRNA (tRNA Sec ) which initiates metabolic pathway that enables translational incorporation of selenocysteine into selenoproteins .…”
Section: Introductionmentioning
confidence: 99%
“…Our comprehensive and detailed research of plant SerRSs in terms of their localization, substrate recognition, and fidelity revealed new interesting insights into function of plant aaRSs . The organellar SerRS dually targeted to both mitochondria and plastids emerged as a new important player in the plant organellar protein quality control .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research on plant SerRSs revealed their cellular localization [11,15], substrate specificity [16][17][18][19], fidelity [20], gene expression during abiotic stress [21], and protein interactor of the cytosolic enzyme [10,22]. Arabidopsis cytosolic SerRS belongs to the bacterial type of SerRS enzymes found in most archaea, bacteria, and eukaryotes [23]. Interestingly, the discovered disulfide bond in the crystal structure of Arabidopsis SerRS (PDB ID: 6GIR) is not found at that position in the crystal structures of SerRSs whose structures have been solved until now [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39].…”
mentioning
confidence: 99%